PENGEMBANGAN JURUSAN PARIWISATA BUDAYA DI PERGURUAN TINGGI HINDU - KETUT SUMADI (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Tourism development is a human quality improvement effort undertaken in a sustain able manner, by utilizing the advancement of science and technology and with regard to global developments. Development of cultural tourism in Indonesia with regard art and culture, natu ral resources and local knowledge. As a basis for tourism development, then the purpose of tourism development is to introduce, utilize, conserve, and enhance the quality and appeal of travel, maintain norms, religious values, cultural life and natural sound environment, prevent negative influences that can generated by tourism activities, and improve social welfare. In the development of the tourism happens variety of impact or influence on the lives of people around the attractions, so it is necessary that efforts be made to respond, anticipating or responding to these influences, both positive and negative. This effort is important to do so tourism can provide benefits, happiness, and prosperity kapada community, nation and state in accordance with the concept of development of cultural tourism in Indonesia as well as the tourism world with the concept of sustainable tourism and community based tourism. One of them through the development of tourism science in institutions of tourism education tourism studies or formal and informal, both at the high school and in college. The problem, whether in Hindu College Tourism Programs can be developed? The problem is discussed in this paper in an effort to increase the participation of Hindus in Tourism Development in Indonesia, while improving the welfare of Hindus through kepariwisataaan.